2018
DOI: 10.2147/mnm.s104793
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase in the cardiovascular remodeling of hypertension: current insights and therapeutic potential

Abstract: Hypertension induces maladaptive vascular and cardiac remodeling, which are related to rearrangement of the extracellular matrix (ECM) and cell hypertrophy and migration. Matrix metalloproteinases (MMPs) are zinc-dependent proteases involved in tissue remodeling mainly by the proteolysis of ECM components. Increased MMP-2 activity is also involved in the proteolysis of important intracellular targets in cardiomyocytes and vascular smooth muscle cells (VSMC). Troponin I and calponin-1 are some of the targets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 93 publications
(130 reference statements)
1
9
0
Order By: Relevance
“…Gelatinase-A (MMP-2) is constitutively expressed in the heart while gelatinase-B is an inducible protease, and we conducted our further study with gelatinase-B due to its inducible response to various stimuli [ 48 ]. Indeed, elevated levels of gelatinase-B have been proposed as a serological cardiac stress marker as its expression increases markedly in diabetic cardiomyopathy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinase-A (MMP-2) is constitutively expressed in the heart while gelatinase-B is an inducible protease, and we conducted our further study with gelatinase-B due to its inducible response to various stimuli [ 48 ]. Indeed, elevated levels of gelatinase-B have been proposed as a serological cardiac stress marker as its expression increases markedly in diabetic cardiomyopathy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the large family of MMPs, MMP-2 (or Gelatinase-A), which is constitutively expressed in the heart and vessel wall, and MMP-9 (or Gelatinase-B), an inducible protease whose presence in tissues is associated with the infiltration of inflammatory cells, when changed in their activities or concentrations, contribute to the proteolysis of structural and contractile proteins of ECM, cardiomyocytes, and VSMCs, leading to maintenance of high BP and CVD development and progression. 3,11,[23][24][25][26] Starting from this evidence, many studies and clinical trials [25][26][27][28] observed a notable higher MMP-9 serum levels in hypertensive patients compared to normotensive controls. [27][28][29][30] In the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) study, Tayebjee and collegues 29 demonstrated that in uncontrolled hypertensive patients (eg, stage 3 of HT) circulating plasma concentrations of MMP-9 and TIMP-1, measured by ELISA, were significantly higher compared to normotensive controls at baseline.…”
Section: Mmps and Systemic Arterial Hypertensionmentioning
confidence: 95%
“…9,10 Moreover, increased MMPs activity has also been associated with intracellular effects in cardiomyocytes and VSMCs, altering the smooth muscle tone. 11 In the last years, several clinical [12][13][14] and experimental studies [15][16][17] highlighted the role of altered activity and/or concentration of specific MMPs and their inhibitors in the pathogenesis of HMOD. They are proposed as reliable biomarkers and potential pharmacological targets to treat or prevent many cardiovascular and renal complications in patients affected by HT.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to a combination of reduced redundancy between MMPs in zebrafish and their more rapid development providing less opportunity for compensatory mechanisms to mitigate the loss of Mmp2 activity [27]. Gelatinase A is among the MMPs found intracellularly [19,21,22,28], and it has been the focus of significant attention in the context of ischemia/reperfusion injury in cardiac muscle [29][30][31][32]. In human and murine myocytes, immunogold localization suggests it is concentrated in the sarcomeres at the Z-discs [19,22].…”
Section: Of 15mentioning
confidence: 99%
“…Once activated, gelatinase A degrades several sarcomeric proteins, resulting in loss of contractility [31,34]. The upshot of this is that inhibition of gelatinase A activity is a promising avenue for mitigating the damage of ischemia/reperfusion injury in a clinical setting [30][31][32], but the question of why this potentially dangerous protease accumulates within the myocytes in the first place -i.e., what, if any, physiological functions does gelatinase A have in the sarcomere -remains unaddressed.…”
Section: Of 15mentioning
confidence: 99%